KEPADATAN POPULASI Orthetrum sabina ( Odonata: Libellulidae) PADA PERTANAMAN PADI SAWAH DI KANAGARIAN AIR BANGIS KECAMATAN SUNGAI BEREMAS KABUPATEN PASAMAN BARAT - Aprianti, Riza; Jasmi, Jasmi; Lusi Zeswita, Armein (STKIP PGRI Sumbar, 2014)
ABSTRACT Dragonflies (Odonata) is a species insect that have numbered middle until large and attractive colour. Type of dragonflies Orthetrum sabina have much and found in Java island, and they as predator insect. The goals of this research is would like to know the population of Orthetrum sabina (Odonata; Libellulidae) in Kanagarian air Bangis, Sungai Beremas district, Pasaman Barat Regency. The research was conducted in Februari 2014. This research is survey descriptive research. Sample of research done for 1 week with condition rice field that flooded and dry land are 3 days in the light months and 3 days in dark month. From the result of population Orthetrum sabina in Kanagarian Air Bangis found that characteristics of Orthetrum sabina average abdomen length 29-30 mm and body length 50-53 mm have compound eyes green colour with slender abdoment. Totally population of Orthetrum sabina in wet rice field (0,99 indvidu/ m2) higher than dry land rice (0,76 individu/ m2). Meanwhile, average population density in the light month (0,94 individu/ m2) higher than in the dark month (0,77 individu/ m2).